Mass immigration, real wages and employment: a Keynesian model - Dancourt, Oscar (2018)
The mass arrival of Venezuelan immigrants escaping the macroeconomic catastrophe caused by the Maduro government is a unique event in Peru’s recent economic history. This text uses a Keynesian model, where employment depends on aggregate demand, in an attempt to identify the two channels through which mass immigration reduces, in the short term, employment and real wages. These two channels are the increase in the labor force, which reduces nominal and real wages; and the decrease in employees’ propensity to consume if immigrants substitute local workers in the labor market.Venezuelan workers bear no responsibility whatsoever for bringing about this situation. Like the many Peruvians who have emigrated since the 1980s, they only look for the best for their families. All of the responsibility lies with the Kuczynski government and its policy of free immigration, which artificially extends the surplus of urban labor in the Peruvian economy